Chromatin, Epigenetics and Plant Physiology - Fojtová, Miloslava; Fajkus, Jiří (International journal of molecular sciences, 2020)
The ever-increasing interest in epigenetics comes from the fact that in the diverse life situations of organisms, e [...].
Keywords: Plants; Chromatin; epigeneze genetická; DNA Methylation; metylace DNA; Epigenesis, Genetic; chromatin; rostliny; Protein Processing, Post-Translational; posttranslační úpravy proteinů